Implementasi Metode Analythic Hierarcy Process (AHP) - Technique for Other Preference by Similiarity to Ideal Solution (TOPSIS) untuk Perangkingan Hasil Kerja Pegawai Collection Bank BTN - Wahyu Dwiky Rahmadan; Nurul Hidayat; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In suppressing the growth of non-performing loans (NPL), Bank industries focuses on debtors who neglect or forget to make payments, so that the Bank collects payments every month. To get maximum results from employees who manage billing in the field, one of them is done by ranking employee performance. The ranking is done to fill spending to become the employee with the first rank. Bank BTN assesses all billing sections with a simple system using Microsoft Excel. This study was conducted by using the AHP-TOPSIS method to rank region 1 of Bank BTN in order to assess the performance of CCRD employees. The Analytical Hierarchy Process method is a method of making decisions by making comparisons between choice criteria and also pair comparisons between existing choices. The TOPSIS method is based on the concept that the best chosen not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution from a geometric point of view by using the Euclidean distance to determine the closeness of an approximation to the optimal solution. The results of the tests that have been carried out, obtained an overall final average of 86,38889%.